Princípios para a criação de uma extensão de metadados sobre interações ecológicas na agrobiodiversidade para o padrão Darwin Core - Filipi Miranda Soares (2019)
Information is an intrinsic element to human relations. When transmitted or stored in digital media, it needs to be well described so it can be efficiently retrieved, accessed and interpreted by society. Among the themes of interest to society today, agrobiodiversity is a broad concept that involves organisms and ecosystems related to agricultural production and crops. For computational systems, the representation of information produced about agrobiodiversity can be done with metadata. However, the existing metadata standards do not fully include the representation of some concepts of agrobiodiversity, as in the Darwin Core (DwC) standard. The aim of this research was to present principles for the creation of an extension of metadata for the DwC standard, having as scope the ecological interactions in the context of agrobiodiversity. To achieve the research aim, the methodology, characterized as exploratory, qualitative, applied and descriptive, was divided into two stages: 1) exploration of methodological and terminological inputs; 2) terminological definition and metadata modeling. The execution of the first stage of the methodology was organized into four substeps: a) systematic analysis of the literature on ecological interactions; b) analysis of the main core of DwC terms; c) analysis of the extensions to the DwC metadata standard; d) correlated terminological analysis of the classes of the model <onto.biodiversity>, DwC and concepts of ecological interactions. The first substep resulted in a conceptual model on ecological interactions; the second substep resulted in the translation of the definitions of the terms of the main core of the DwC and respective analyzes; the third substep presented a summary of the content of the metadata extensions developed for DwC in other projects; and, finally, the fourth substep consisted of analyzing in a correlated manner the classes of the <onto.biodiversity> model, which was developed by Embrapa in order to organize information on agrobiodiversity, the DwC term classes and their extensions and the conceptual model of ecological interactions. The second stage of the methodology resulted in three metadata elements, created to represent the interaction of parasitism, represented as a metadata record in Extensible Markup Language (XML). It is considered that the greatest contribution of this research was to present a set of methodological principles for the creation of an extension of metadata for the representation of ecological interactions in the context of agrobiodiversity, which can foster improvements in agricultural practices, which are important for the entire community. society, as well as for the field of information science studies.